Strangeness in astrophysics and cosmology - Boeckel, Moritz Tillmann; Hempel, Marius; Sagert, Irina; Pagliara, Giuseppe; Saʿd, Basil A.; Schaffner-Bielich, Jürgen (Journal of physics. G, Nuclear and particle physics, 2010)
Some recent developments concerning the role of strange quark matter for astrophysical systems and the QCD phase transition in the early universe are addressed. Causality constraints of the soft nuclear equation of state as extracted from subthreshold kaon production in heavy-ion collisions are used to derive an upper mass limit for compact stars. The interplay between the viscosity of strange quark matter and the gravitational wave emission from rotation-powered pulsars are outlined. The flux of strange quark matter nuggets in cosmic rays is put into perspective with a detailed numerical investigation of the merger of two strange stars. Finally, we discuss a novel scenario for the QCD phase transition in the early universe, which allows for a small inflationary period due to a pronounced first-order phase transition at large baryochemical potential.
Gesehen am 26.01.2023